1995
DOI: 10.1115/1.2831233
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Feedline and the Hydrostatic Pocket Depth on the Flow Pattern and Pressure Distribution

Abstract: The paper treats on a comparative basis the development of the flow and pressure maps in deep, and respectively, shallow hydrostatic bearing pockets. The numerical simulation uses a dimensionless formulation of the Navier-Stokes equations written for a body fitted coordinates system, and applied through a collocated grid. The present work is a continuation of the simulations performed by Braun et al. (1993, 1994a, 1994b) to cases where the length and diameter of the restrictor feedline is of consequence to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Helene et al (21), in their two-dimensional studies of hydrodynamic journal bearing (HJB) pockets, reported similar results, but the open HJB literature does not contain much more information regarding these unusual profiles. Rather, one finds a very homogeneous set of reports whereby the pressure profile is either constant or ramped and contains a small peak at the point of jet impact on the shaft (Braun and Dzodzo (18), (24); San Andrés and Velthuis (26); Chaomleffel and Nicolas (27); Bou-Said and Chaomleffel (28) and others). To further verify and confirm the present results, a parametric numerical simulation using viscosity and clearance as the leading parameters has been performed.…”
Section: Conclusion About Jet Pressure Profilesmentioning
confidence: 96%
“…Helene et al (21), in their two-dimensional studies of hydrodynamic journal bearing (HJB) pockets, reported similar results, but the open HJB literature does not contain much more information regarding these unusual profiles. Rather, one finds a very homogeneous set of reports whereby the pressure profile is either constant or ramped and contains a small peak at the point of jet impact on the shaft (Braun and Dzodzo (18), (24); San Andrés and Velthuis (26); Chaomleffel and Nicolas (27); Bou-Said and Chaomleffel (28) and others). To further verify and confirm the present results, a parametric numerical simulation using viscosity and clearance as the leading parameters has been performed.…”
Section: Conclusion About Jet Pressure Profilesmentioning
confidence: 96%
“…The linear pressure variation in the recess is due to the translation or Couette flow effect and the contrast between Couette-dominated and injection-dominated flow has been discussed for the two-dimensional case on several occasions (e.g. Braun & Dzodzo, 1995). In practice, it is more common to prescribe the injection pressure and not the injection flow rate.…”
Section: Discussionmentioning
confidence: 99%
“…A good place to start is the Navier-Stokes simulation conducted by Braun & Dzodzo (1995) for a two-dimensional journal bearing. Their study presents detailed results for the pressure distribution and streamlines in the two basic flow regimes: a flow dominated by the Couette effects and a case dominated by the flow due to lubricant injection.…”
Section: Limitation Due To Inertial Effectsmentioning
confidence: 99%
“…Some good examples can be found in literature. [10][11][12][13][14] Normally, the injection (hydrostatic) pressure is treated by the cited authors as constant and the effect of deep and shallow pockets geometries on the pressure and flow profiles are investigated. In the present work, the injection pressure is treated as constant as well as time dependent, in order to simulate different schemes of application of the active lubrication concept.…”
Section: Introductionmentioning
confidence: 99%